Study on Transverse Strength of the Deck-Container Ships due to Laying All Containers on Deck - Rosmani Munandar; Andi Ardianti; Ganding Sitepu; Andi Mursid Nugraha; Hamzah Hamzah; Muhammad Ichsan Hayatuddin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
The strength of transversal structure of the ship has a great effect on the safety of ship. Shipswill experience conditions that affect the strength of the ships structure. A deck-container ships are the ships that all container are loaded on deck such as MV. Khendaga Nusantara series ships. The transversal strength of the ships is loaded mainly by the weight of cargolaying on deck.. This research aims to determine the transverse strength of a deck-container ship due to the all container loads on deck. The research was done by usingfinite element method throughmodeling transverse ship structure, the simulation is conducted by varying the amount and lay-out of containers on dec). The loads appliedto the model are side loads, bottomloads, and deck loads in according to BKI rules. The results shows that the stress that occurred in the web frame was 140,63 N/mm2due to the placement of the entire container on the deck(full loading). For ship structure response, a deformation of 2,86 mm occurred in the web frame area at maximum loading. Stress ratio that occurs in all ship’s structuredoes not exceed 1 in other words the working stress does not exceed the allowedstress according to BKI rules.